Blood flow restriction training and Betaine supplementation as a novel combined modality to augment skeletal muscle adaptation: A short review - Machek, S. B.; Cardaci, T. D.; Willoughby, D. S. (Strength and Conditioning Journal, 2021)
Blood flow restriction (BFR) training and betaine supplementation are emerging training tools with growing evidence, potentially providing a synergistic stimulus to augment skeletal muscle adaptation. Betaine may facilitate stretch-mediated anabolism secondary to BFR-induced extracellular-to-intracellular fluid influx, whereby their combination may promote a new, low-barrier avenue for athletes and clinical practitioners to elicit hypertrophy and strength. This review aims to (a) demonstrate existing evidence on BFR- and betaine-mediated skeletal muscle growth, (b) provide rationale for their combination as a superior anabolic stimulus, and (c) advocate for athletes and the elderly as prime demographics for a potentially valuable BFR-betaine synergistic therapy.